The selection of the amount of anthracene derivatives from raw materials of plant origin and the study of their influence on the rat periodontal - Schneider, S. A.; Suslova, O. V.; Tkachenko, E. K.; Nikolaenko, K. V. (Journal of Education, Health and Sport, 2019)
The article presents a new method of ethanol extraction of anthracene derivatives from the herb St. John's wort, the total content of which was evaluated using a calibration graph. The drug improved mineral metabolism, showed anti-inflammatory effects in the bone tissue of the periodontal rats.